FACTORS THAT INFLUENCE THE OCCURATION OF ARI DISEASE IN TOLLS IN RANTANG PUSKESMAS, MEDAN CITY - Yosua Riva Naldy Panjaitan; Masdalena -; Suhartina - (PRIMER (Prima Medical Journal), 2022)
Background: ARI is an acute infection that attacks the respiratory tract, namely body organs starting from the nose to the alveoli along with the adnexa (Romelan, 2006). Acute Respiratory Infection (ARI) is one of the causes of death that is often experienced by children in developing countries. Hypothesis: What are the factors that influence the occurrence of ARI in children under five at the Rantang Health Center, Jalan Rantang No.37, Sei Putih Tengah, Medan City. Research Methods: This research is descriptive analytic with a cross-sectional approach (cross-sectional). This study used a questionnaire which was distributed to each respondent's parents. Summary of Results: The age of children under five who suffer from ARI at the Rantang Public Health Center in Medan is the most aged >2 years - 5 years with the most gender being male. The level of knowledge of the child's parents is less, with an average level of low education, has a low level of information, and has less environmental factors